PERSEPSI PENONTON PEREMPUAN TENTANG KARAKTER ROMANTIS FILM DILAN 1990 - Mukhammad Syafi’ul Umam; Ririn Risnawati; Rizki Budhi Suhara; Lisna Novita (JIKE: Jurnal Ilmu Komunikasi Efek, 2020)
This study aims to determine how the female audience's perception of the romantic character of the 1990 film Dilan. This research is a qualitative research using qualitative descriptive method. Data collection techniques used in this study are observation, interview and documentation techniques. The results of this study indicate that the romantic character of the Dilan 1990 film teaches about a good relationship must be brave to be different and romantic, giving the perception that the relationship must be lived uniquely so that a harmonious relationship can be established, the relationship must have firmness, especially for a man who must make the right decision and have to be romantic towards the partner, the relationship must be sincere, and increase friends to hang out and there must be a humorous attitude, the relationship does not have to be luxurious and there must be proof by real action and love there must be a sense of comfort, trust and support . The informants have provided different information about the perception of the Dilan 1990 film and they have learned a lot from the 1990 Dilan film about the importance of trust, support and comfort. Keywords: Perception, Audience, Women, Romantic Characters, Dilan 1990 Movie